Challenges for optimizing real-world evidence in Alzheimer’s disease: The ROADMAP Project - Gallacher, J; De Reydet De Vulpillieres, F; Amzal, B; Angehrn, Z; Bexelius, C; Bintener, C; Bouvy, J; Campo, L; Diaz, C; Georges, J; Gray, A; Hottgenroth, A; et al. (IOS Press, 2019)
ROADMAP is a public-private advisory partnership to evaluate the usability of multiple data sources, including real-world evidence, in the decision-making process for new treatments in Alzheimer's disease, and to advance key concepts in disease and pharmacoeconomic modeling. ROADMAP identified key disease and patient outcomes for stakeholders to make informed funding and treatment decisions, provided advice on data integration methods and standards, and developed conceptual cost-effectiveness and disease models designed in part to assess whether early treatment provides long-term benefit.